Improvement of ultraviolet pasteuriser for production of pineapple fruit juice - Mansor, Atikah (2015)
Currently, the existing ultraviolet (UV) pasteuriser cannot achieve the FDA standard which is 5 log10 reductions of microorganisms in tropical fruit juice because of the high soluble content in the tropical fruit juice. Therefore, a new ultraviolet pasteuriser was designed which it was able to inactivate microorganisms in tropical fruit juice up to 5 log10 reduction. This study aims to develop an ultraviolet pasteuriser which able to inactivate microorganisms with at least 5 log10 reductions in pineapple fruit juice and maintain the quality attributes of juice for SME industry. A new designed UV pasteuriser was developed based on Dean Vortex technology with an additional UV light to give extra UV radiation to the juice. The experiment was conducted using the UV pasteuriser which the UV lamp was not enclosed with quartz glass (UV pasteuriser (without quartz)) and UV pasteuriser that UV lamp was enclosed with quartz glass (UV pasteuriser (with quartz)). For both pasteurisers, two difference frequencies was tested which are at 30 Hz and 40 Hz to investigate the effect of difference flow rate on quality of pineapple juice based on the physico-chemical and the microbial analyses. The result showed the UV pasteuriser (with quartz) at frequency of 30 Hz (flow rate of 0.00153 L/s) and UV-C dosage of 64.11 mJ/cm2 was showed better quality based on physico-chemical results and able to inactivate Salmonella typhimurium up to 5.91 log CFU/ml. The UV pasteuriser (without quartz) was slightly affected the quality of juice because none installation of quartz glass at the UV-C lamp was affected the quality attributes of juice. The lightness (L-value) and total soluble solid (TSS) of juice after treated with UV pasteuriser (with quartz) at 30 Hz was not significantly changes comparing to untreated juice. Meanwhile, the Chroma, hue angle and ascorbic acid content were significantly changes compare to the untreated juice. However the range of ascorbic acid was fall in slightly noticeable range thus, it can be negligible. The turbidity of juice treated with UV pasteuriser (with quartz) was significantly difference than untreated juice. During 9 weeks of storage, the TSS, L-value, hue angle, Chroma, ascorbic acid content and turbidity of untreated and UV pasteurised (with quartz) juice were give a significant decreased whereas their titratable acidy (TA) were not significantly decreased during storage. There is no significant increase of pH of untreated and UV pasteurised (with quartz) juices during storage. Regarding the microbiological analysis, count of Salmonella typhimurium was significantly increased after nine weeks of storage at 4±1°C. Other than that, the pineapple juice that was treated by ultraviolet pasteuriser (with quartz) was able to extend the shelf life of pineapple juice from 2 weeks to 5 weeks longer. Therefore, these results on physico-chemical and microbiological analysis was demonstrate the effectiveness of UV pasteuriser (with quartz) in preserving the nutritional attributes and inactivate microorganisms in pineapple fruit juice which achieved the FDA standard.